UTKIR HOSHIMOV'S WORKS: MORAL INTERPRETATION OF PARENT-CHILD RELATIONSHIPS (International journal of artificial intelligence, 2025)
This article examines the moral and ethical aspects of parent-child relationships in O'tkir Hoshimov's literary works. Through comprehensive literary analysis, the study explores how the author portrays family values, moral obligations, and intergenerational relationships in Uzbek society. The research highlights the didactic significance of Hoshimov's works in understanding traditional family dynamics and their contemporary relevance.